2018
DOI: 10.1186/s13756-018-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of high drug resistant bacterial isolates from patients with health care associated infections at Jimma University medical center: a cross sectional study

Abstract: BackgroundThe rates of resistant microorganisms which complicate the management of healthcare associated infections (HAIs) are increasing worldwide and getting more serious in developing countries. The objective of this study was to describe microbiological features and resistance profiles of bacterial pathogens of HAIs in Jimma University Medical Center (JUMC) in Ethiopia.MethodsInstitution based cross sectional study was carried out on hospitalized patients from May to September, 2016 in JUMC. Different clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 31 publications
(35 reference statements)
13
70
9
Order By: Relevance
“…However, the current result was higher than of the study findings reported from Jima Ethiopia (51%) [17] and of study conducted in Algeria (47.6%) [18] and lower than reported from a tertiary care hospital in Riyadh capital Saudi Arabia (72%) [19]. These indicate that the distribution of ESBL producing organisms vary from region to region and may be higher in certain geographic areas [20].…”
Section: Bacterial Strainscontrasting
confidence: 85%
“…However, the current result was higher than of the study findings reported from Jima Ethiopia (51%) [17] and of study conducted in Algeria (47.6%) [18] and lower than reported from a tertiary care hospital in Riyadh capital Saudi Arabia (72%) [19]. These indicate that the distribution of ESBL producing organisms vary from region to region and may be higher in certain geographic areas [20].…”
Section: Bacterial Strainscontrasting
confidence: 85%
“…Six studies were found in Addis Ababa [ 19 21 , 23 , 25 , 31 ], five studies in Amhara region [ 8 , 16 , 26 , 27 , 29 ], five studies in Oromia [ 9 , 17 , 18 , 28 , 30 ], one study both in Addis Ababa and Southern Nation Nationalities and People Region (SNNPR) [ 22 ], one each in Tigray [ 24 ] and SNNPR [ 10 ]. Nine studies were conducted across all age groups.…”
Section: Resultsmentioning
confidence: 99%
“…β-lactam resistance is an increasing problem for the infection treatment, thereby, use of carbapenem antibiotics for treatment of infections caused by EEBL producing microorganisms was implemented. Nevertheless, carbapenem resistant strains have been reported, elevating patients’ mortality index (15).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance is associated with the expression of genes contained in plasmids, transposons and integrones which are key elements in horizontal genetic material transference. Klebsiella carbapenem resistance has been principally associated with plasmids (15, 17).…”
Section: Discussionmentioning
confidence: 99%